Digital assistant prototype for humanization in health services “IPS Popayán, Cauca.” - Rosero Torres, Ariadna
Objective. Develop an animated digital assistant prototype to be incorporated into an appointment management platform in the admissions service and guide the user in an IPS. Method. Qualitative probabilistic study, with cross-sectional experimental design with a confidentiality sample size of 95%, acollection instrument is applied, an animated digital assistant prototype is designed, and the final product is validated. Results. In the present research project three main results were obtained. Two surveys carried out with personnel from the user service area and IPS users, the Design and programming of the animated digital assistant prototype and the validation of the product. Conclusions. The development of this research has given us a functional prototype model, an animated digital assistant that provides humanized tics to educate the personnel in the health care user area, taking as a basis for its educational content the health care protocol for the citizen and reinforcing shortcomings found in the collection of information